2021
DOI: 10.3389/fphys.2021.716981
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Different Plyometric and Strength Exercises on Balance Performance in Youth Weightlifters

Abstract: Background: High-intensity muscle actions have the potential to temporarily improve the performance which has been denoted as postactivation performance enhancement.Objectives: This study determined the acute effects of different stretch-shortening (fast vs. low) and strength (dynamic vs. isometric) exercises executed during one training session on subsequent balance performance in youth weightlifters.Materials and Methods: Sixteen male and female young weightlifters, aged 11.3±0.6years, performed four strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Furthermore, the NMT implemented in the current study also included plyometric exercises, widely used by athletes in different sports specialties to increase strength and explosiveness of muscles (Davies et al, 2015). Researchers showed that plyometric training, induces several benefits, including improvements in vertical jump, acceleration, agility, muscle strength, and power performance, as well as enhancement in joint awareness, proprioception and PB (Davies et al, 2015; Ramirez‐Campillo et al, 2020; Werfelli et al, 2021; Zamani et al, 2010). Combining these three training modalities could optimise PB improvement in these athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the NMT implemented in the current study also included plyometric exercises, widely used by athletes in different sports specialties to increase strength and explosiveness of muscles (Davies et al, 2015). Researchers showed that plyometric training, induces several benefits, including improvements in vertical jump, acceleration, agility, muscle strength, and power performance, as well as enhancement in joint awareness, proprioception and PB (Davies et al, 2015; Ramirez‐Campillo et al, 2020; Werfelli et al, 2021; Zamani et al, 2010). Combining these three training modalities could optimise PB improvement in these athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate a significant, acute effect of MHJ on balance performance compared to SHJ in youth volleyball players. Using maximal plyometric action, the specificity of the exercises induce a training stress on stability ( Lauber et al, 2021 ; Werfelli et al, 2021 ). In respect to balance performance the results of the present study are not unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…With reference to the study of Werfelli et al (2021) on the acute effects of different plyometric and strength exercises on balance performance in youth weightlifters, an a priori power analysis, with a type I error rate of 0.05 and 80% statistical power, was computed. The analysis indicated that 24 participants would be sufficient to observe a significant interaction effect [effect size Cohen’s f = 0.3 for the center of presser velocity (CoP V) on unstable surface (i.e., BOSU ball with flat side facing up)].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…adductors and abductors, or hip flexors and extensors or all muscles of the lower limb). Therefore, the positive effects observed may not necessarily reflect the stretching phase of the PNF, but rather the contraction, which could have determined increased strength and therefore increased ability to balance [ 83 ]. Indeed, the only study applying PNF to a single group of muscles, more specifically the hamstrings (as in the present investigation), observed no increase in balance in neither the anterior–posterior nor medio-lateral directions [ 84 ].…”
Section: Discussionmentioning
confidence: 99%